2020
DOI: 10.1007/s11001-020-09404-y
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on morphology and genesis of giant and mega pockmarks near Andu Seamount, Nansha Region (South China Sea)

Abstract: Pockmarks consists of depressions on the seafloor and are often considered to originate from fluid escape activities. In this study, we report 125 pockmarks near the Andu Seamount in the southern margin of the South China Sea (SCS) and preliminarily investigate their genesis based on multi-beam bathymetry and multichannel seismic reflection data. Most of them are giant and mega pockmarks and display circular, elliptical, elongated, crescent, comet and irregular shapes on a plan-view. The mapped pockmarks cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Seafloor depressions are common geomorphological features in marine and lacustrine environments around the globe. Among them, large-scale depressions are characterized by hundreds of meters in diameter and several tens of meters in depth as described, e.g., for the Lower Congo Basin (e.g., Pilcher and Argent, 2007;Sahling et al, 2008;Nöthen and Kasten, 2011;Kasten et al, 2012;Wenau et al, 2017), Chatham Rise off New Zealand (Davy et al, 2010;Collins et al, 2011;Klaucke et al, 2018), the South China Sea (Zhang et al, 2020), and the Korean Peninsula shelf (Cukur et al, 2019). The origin and preservation mechanisms of seafloor depressions, in general, are ascribed to several different processes; however, especially for complex, large-scale depressions, these are often elusive (King and MacLean, 1970;Hovland and Judd, 1988;Judd and Hovland, 2007;León et al, 2010;Cukur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Seafloor depressions are common geomorphological features in marine and lacustrine environments around the globe. Among them, large-scale depressions are characterized by hundreds of meters in diameter and several tens of meters in depth as described, e.g., for the Lower Congo Basin (e.g., Pilcher and Argent, 2007;Sahling et al, 2008;Nöthen and Kasten, 2011;Kasten et al, 2012;Wenau et al, 2017), Chatham Rise off New Zealand (Davy et al, 2010;Collins et al, 2011;Klaucke et al, 2018), the South China Sea (Zhang et al, 2020), and the Korean Peninsula shelf (Cukur et al, 2019). The origin and preservation mechanisms of seafloor depressions, in general, are ascribed to several different processes; however, especially for complex, large-scale depressions, these are often elusive (King and MacLean, 1970;Hovland and Judd, 1988;Judd and Hovland, 2007;León et al, 2010;Cukur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The good coherence in orientation between collinear pockmarks and faults further supports the close relationship between the regional structural setting and the local fluid escaped patterns, which, in turn, control pockmark configuration and spatial distribution. At similar sites where the structural setting dominates, a pockmark field configuration has been reported, such as in the Barents Sea [27], Ireland [29] and the Nasha Region of the South China Sea [105].…”
Section: Relation To Faults and Subsurface Characteristicsmentioning
confidence: 76%
“…In addition to the northern slope of the South China Sea, a few possible cold seeps are indicated in the southern South China Sea, e.g., methane seepage is inferred from the porewater geochemistry of shallow sediments in the Beikang basin . Zhang K et al (2020) reported 125 pockmarks close to the Andu seamount in the southern margin of the South China Sea. To date, cold seeps remain poorly investigated in the southern South China Sea.…”
Section: Seabed Fluid Flow In the South China Seamentioning
confidence: 99%